Cardioprotective Effect of Rheum turkestanicum Against Doxorubicin-Induced Toxicity in Rats - Hosseini, Azar; Safari, Mohammad-Kazem; Rajabian, Arezoo; Boroumand-Noughabi, Samaneh; Eid, Ali H.; Al Dhaheri, Yusra; Gumpricht, Eric; Sahebkar, Amirhossein (Frontiers in Pharmacology, 2022)
Background: Doxorubicin as an anti-cancer drug causes cardiotoxicity, limiting its tolerability and use. The mechanism of toxicity is due to free radical production and cardiomyocytes injury. This research evaluated Rheum turkestanicum (R.turkestanicum) against doxorubicin toxicity due to its considerable in vitro antioxidant activity. Methods: Male Wistar rats received 2.5mg/kg doxorubicin intraperitoneally every other day for two weeks to create an accumulative dose. R.turkestanicum was administrated at a dose of 100 and 300 mg/kg intraperitoneally from the second week for seven days. On the 15th day, the animals were anesthetized and blood collected from cardiac tissue for evaluation of alanine aminotransferase (ALT), aspartate aminotransferase (AST), cardiac muscle creatinine kinase (CK-MB), troponin T (cTn-T), lactate dehydrogenase (LDH), and B-type natriuretic peptide (BNP). A cardiac homogenate was also collected to determine superoxide dismutase (SOD), catalase (CAT), malondialdehyde (MDA), and thiols. Histopathology was also performed. Results: Doxorubicin increased all cardiac enzymes and MDA, correlating with a reduction in SOD, catalase, and thiols. Histopathology revealed extracellular edema, moderate congestion, and hemorrhage of foci. In contrast, administration of R.turkestanicum ameliorated these doxorubicin-induced pathophysiological changes. Conclusion: This study revealed that the extract ameliorated doxorubicin-induced cardiac toxicity via modulation of oxidative stress-related pathways. Liquid chromatography-mass spectrometry analysis of R.turkestanicum indicated several components with potent pharmacological properties.